Contralateral prophylactic mastectomy: A qualitative approach to exploring the decision making process. Issue 2 (4th March 2018) - Greener, Judith R.; Bass, Sarah Bauerle; Lepore, Stephen J.
ABSTRACT: The proportion of women with unilateral breast cancer and no familial or genetic risk factors who elect contralateral prophylactic mastectomy (CPM) has grown dramatically, even in the absence of clear data demonstrating improved outcomes. To further extend the literature that addresses treatment decision-making, qualitative interviews were conducted with eleven women who considered CPM. A social ecological model of breast cancer treatment decision-making provided the conceptual framework, and grounded theory was used to identify the cognitive, psychosocial, and emotional influences motivating treatment choice. This research identified five themes that give context to women's decision-making experience: (1) variability in physician communication, (2) immediacy of the decision, (3) meaning of being proactive about treatment, (4) meaning of risk, and (5) women's relationship with their breasts. The results suggest that greater emphasis should be placed on a more nuanced understanding of patients' emotional reaction to breast cancer and managing the decision-making environment.